Growth Performance of Eucalyptus Microtheca Seedlings in Response to Different Levels of Organic and Inorganic Fertilizer - Sherzad Omar Hamad; Aisha Abdulla Shahin (QALAAI ZANIST SCIENTIFIC JOURNAL, 2022)
In nursery stage, some silvicultural treatments have been applied to produce high quality of forest seedlings. Fertilizer application is one of the most significant treatments that effects on the growth and development of the seedlings. This study was performed in early November 2019 to early April 2020.The paper evaluates the effects of organic and inorganic fertilizers on the growth of Eucalyptus microtheca seedling under nursery growing conditions. Organic fertilizer was used with three levels of animal manure, which are 0, 50 and 100 g/pot, and three levels of inorganic (compound chemical) fertilizer, which include 0, 1 and 2 g/pot of NPK (15:15:15), and each treatments were replicated three times due to availability limited numbers of Eucalyptus microtheca seedlings in the nursery. Vegetative growth parameters taken include, seedling height (cm), leaf number, stem diameter (mm) and biomass (g). The results obtained from the experiment showed that the effects of the treatments were significantly difference from the control for all the parameters accessed. Results of this research concluded that the best seedling growth performance and biomass allocation of E. microtheca were obtained from the seedlings that fertilized with 50 g organic matter and 2 g NPK fertilizer. The results will help nursery man to produce healthy and a high quality of E. microtheca seedlings to meet plantation program.